2016
DOI: 10.1073/pnas.1607710113
|View full text |Cite|
|
Sign up to set email alerts
|

CCN1/CYR61-mediated meticulous patrolling by Ly6C low monocytes fuels vascular inflammation

Abstract: Inflammation is characterized by the recruitment of leukocytes from the bloodstream. The rapid arrival of neutrophils is followed by a wave of inflammatory lymphocyte antigen 6 complex (Ly6C)-positive monocytes. In contrast Ly6C low monocytes survey the endothelium in the steady state, but their role in inflammation is still unclear. Here, using confocal intravital microscopy, we show that upon Toll-like receptor 7/8 (TLR7/8)-mediated inflammation of mesenteric veins, platelet activation drives the rapid mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 67 publications
8
94
1
2
Order By: Relevance
“…Agonists for TLR2 and TLR9 induced a strong early recruitment of crawling monocytes within 30 min of stimulation, and an early but weaker response with TLR5 ( Fig. 1A and B), as previously observed for TLR7/8 [6]. Conversely, agonists for TLR3 and TLR4 induced only a late arrival of patrolling monocytes, about 2.5 h after the initiation of inflammation ( Fig.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Agonists for TLR2 and TLR9 induced a strong early recruitment of crawling monocytes within 30 min of stimulation, and an early but weaker response with TLR5 ( Fig. 1A and B), as previously observed for TLR7/8 [6]. Conversely, agonists for TLR3 and TLR4 induced only a late arrival of patrolling monocytes, about 2.5 h after the initiation of inflammation ( Fig.…”
Section: Resultssupporting
confidence: 84%
“…Our results show three kind of kinetics in mesenteric veins: (i) previously reported early recruitment of Ly6C low monocytes followed by late neutrophil arrival (TLR7/8) , (ii) early monocyte and neutrophil recruitment (TLR2, TLR5 and TLR9) and (c) early neutrophils followed by late and weak monocyte recruitment (TLR3 and TLR4).…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…On the other hand, Cyr61 is recognized as a mediator of inflammation [33,35]. Cyr61 enables monocytes recruitment upon vascular inflammation, and endothelial-bound Cyr61 sustains monocyte patrolling under inflammation condition, while blocking Cyr61, impairs early arrival of monocyte and abolishes neutrophil recruitment [34]. Other studies showed that Cyr61 promotes monocyte chemotaxis and macrophage migration, support macrophage adhesion and activates proinflammatory genetic program by activating NFκB-mediated transcription, and upregulating expression of cytokines and chemokines in macrophages [35,36], indicating an important role of Cyr61 in inflammatory responses and its essential role in atherosclerostic pathogenesis.…”
Section: Discussionmentioning
confidence: 99%